"And You Welcomed Me". Issue 1 (1st January 2014) - O'Neill, SJ, William R.; Peter Henriot, SJ
Abstract In this article, I assess rival liberal and communitarian ethical perspectives underlying contemporary debates regarding migration policy in the US. I then propose a critical via media in a rights-based ethics of solidarity with migrants. I conclude by addressing the distinctive role played by citizens of faith in a religiously pluralist polity like our own, noting, in particular, the place (locus) of Christian belief in immigration policy.